SARS-CoV-2 Pathogenesis: Imbalance in the Renin-Angiotensin System Favors Lung Fibrosis - Delpino, María Victoria (2020)
After SARS-CoV-2 infection, a major complication of those who survived to COVID-19 outbreak is the development of severe lung disease leading to pulmonary fibrosis. At earliest step of virus-host cell interaction when the SARS-CoV-2 interacts with the ACE2 receptor highly expressed in pneumocytes type II, a linkage is established between the renin-angiotensin-system (RAS) and the viral pathogenesis. Within this important system, the angiotensin-converting enzyme (ACE) is deputed to the conversion of angiotensin I to angiotensin II (AngII), a potent vasoconstrictive peptide involved directly in inflammation and fibrosis development. AngII is hydrolyzed by ACE2 to Ang1-7, triggering a cascade of events that counteract fibrosis. This imbalance is known to be due to inflammatory damage. However, because ACE2 is the receptor for SARS-Cov-2, we could also speculate that the virus per se could modulate its enzymatic activity. In our opinion the wound healing pathways that mediate tissue repair after SARS-CoV-2 mediated injury, should consider managing the imbalanced ACE/ACE2 axis. We hypothesize that the heptapeptide Ang1-7 could provide novel therapeutic interventions for pulmonary fibrosis patients. Understanding how the RAS, wound healing and other pro-fibrotic pathways act after viral infection should lead to novel therapeutics in the future.